0
$\begingroup$

I am currently woking on some clack online homework problem. I really have no idea how to approach this problem. If someone could help me solve this question I would greatly appreciate it!

From Rogawski ET 2e section 10.7, exercise 31.

Find the Taylor series for $f(x) = \dfrac{1}{1 - 3x}$ centered at $c=1$.

$$\frac{1}{1-3x} = \sum_{n=0}^{\infty} [\textrm{_________}]$$

$\endgroup$
1
$\begingroup$

$$\begin{array} \\ \frac{1}{1-3x} &= \frac{1}{1-3(x-1)-3} \\ &= \frac{1}{-2-3(x-1)} \\ &= -\frac{1}{2} \left( \frac{1}{1 + \frac{3}{2}(x-1)} \right) \\ &= -\frac{1}{2} \left( \frac{1}{1 - (-\frac{3}{2}(x-1))} \right) \\ &= -\frac{1}{2} \sum_{n=0}^\infty \left(-\frac{3}{2}(x-1)\right)^n \textrm{ for } \left|-\frac{3}{2}(x-1)\right|<1\\ &= -\frac{1}{2} \sum_{n=0}^\infty \frac{(-1)^n 3^n}{2^n} (x-1)^n \textrm{ for } \left|x-1\right|<\frac{2}{3} \\ &= \sum_{n=0}^\infty \frac{(-1)^{n+1} 3^n}{2^{n+1}} (x-1)^n \textrm{ for } x \in \left(\frac{1}{3},\frac{5}{3}\right) \end{array}$$

$\endgroup$
0
$\begingroup$

Try writing out the expansion on a piece of paper. It should look like $$\frac{1}{1-3x}=\sum_{n=0}^{\infty}\frac{(-1)^{n+1}(x-1)^n}{2^{n+1}}$$ Now, consider how the $k^{th}$ term and the $k+1^{th}$ term compare.

$$T_k=\frac{(-1)^{k+1}(x-1)^k}{2^{k+1}}$$ $$T_{k+1}=\frac{(-1)^{k+1+1}(x-1)^{k+1}}{2^{k+1+1}}=\frac{(-1)^{k+1}(x-1)^{k}}{2^{k+1}}\frac{(-1)(x-1)}{2}=\frac{(1-x)}{2}T_k=r(x)T_k$$ Obviously $|r(x)|<1$ must hold in order for the sum to converge, requiring $x$ to fall in the interval $(-1,3)$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.